RANCANG BANGUN ALAT PENGUPAS KULIT BAWANG UNTUK PANTI ASUHAN BHAKTI KASIH BOGOR - TOBING, SHEILA (Jurnal Pengabdian Masyarakat Charitas, 2021)
Red onions and garlics are one of the most usual spices that is used in Indonesian food. One of the content inside the onions is sulfur, which can react chemically and form sulfenic acid. Sulfenic acid is one of the chemical compound which can cause sore to redness on human’s eyes. Production process that include pre-harvest to post-harvest requires support of effective facilities, suitable equipment and agricultural machinery so that productivity could be increased. Red onions and garlics peeling in mass number will cost a lot of time and can cause irritation on human’s eyes. Therefore, an onion peeler which can peel a lot of red onions and garlics without human intervention is needed to increase productivity. Bhakti Kasih Orphanage at Bogor provides a home for 55 children from around Indonesia such as Papua, Ambon, Nias, Jakarta and even Timor Leste. Furthermore, there are also 4 caretakers and 7 alumni from Bhakti Kasih Orphanage living with them. Foods that are provided there often use red onions and garlic as base spices, which usually takes 20 minutes per kilogram garlics or red onions to peel the skin off.